Pemanfaatan Potensi Desa Musirlor Melalui Produk UMKM dalam Menyongsong Wisata Bendungan Semantok - Hendra Setiawan; Nurman Ramadhan; Khoirotus Silfiyah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This research will add MSME products located in Musirlor Village, Rejoso District, Nganjuk Regency. We use the method of Asset Based Community Development (ABCD) which means an approach by utilizing the potential of assets in it that intersect with the potential of Tourism. A methodology used to uncover power in society through dialogue with citizens to determine the type of skill. From the results of research through these methods, most of the population in the village Musirlor 50% work as farmers and gardening. Unfortunately, the population here lacks the Giants and skills to produce processed products from agricultural products. Analyzing from these conditions, we innovate to make processed corn named “Japri (Crispy Corn)” and companion products for MSMEs, namely Citronella Oil and (Papi) Crispy papaya. With the Semantok Dam located in the next village, namely Sambikerep village, it will certainly be an area that will be crowded with visitors from out of town, even abroad so that it becomes an opportunity for the surrounding community, especially Musirlor Village which is only 3.5 kilometers from the dam.